Four versus six chemotherapy cycles in endometrial carcinoma with a high risk of recurrence: a retrospective study. (23rd April 2020) - Mayama, Michinori; Asano, Hiroshi; Nomura, Eiji; Ihira, Kei; Nozaki, Ayako; Kato, Tatsuya; Konno, Yousuke; Mitamura, Takashi; Kobayashi, Noriko; Takeda, Mahito; Kudo, Masataka; Watari, Hidemichi
Abstract: Objective: This study compared the survival outcomes and the incidence of chemotherapy-related adverse events in endometrial cancer patients who received four and six cycles of adjuvant chemotherapy to examine the optimal number of adjuvant chemotherapy cycles. Methods: A total of 112 patients with endometrial cancer with a high risk of recurrence were retrospectively enrolled; 46 patients received four cycles and 66 received six cycles of adjuvant chemotherapy. Between-group differences of overall survival, disease-free survival, hematological and non-hematological toxicities were analyzed. Baseline patient's background differences were assessed with inverse probability of treatment weighting using propensity score. Results: Overall and disease-free survivals between the two groups were not significantly different. Paclitaxel + carboplatin, every 3–4 weeks was the most frequently used chemotherapy regimen in both groups. Patients in the six-cycle chemotherapy group developed neutropenia G4 or febrile neutropenia more frequently than those in the four-cycle group; odds ratio (95% confidence interval) is 4.07 (1.51–10.96). Peripheral sensory neuropathy was the most frequently observed non-hematological toxicity; the incidence of peripheral sensory neuropathy was not significantly different between four- and six-cycle chemotherapy group, P = 0.832. The result was same in the subgroup analysis in patients who received TC regimen, P = 0.455. Conclusion: This study implies a possible benefit of fewer cycles of adjuvant chemotherapy in endometrial cancer patients with a high risk of recurrence because of the lower incidence of hematological toxicities without impairing survival outcomes. Abstract : Four cycles of adjuvant chemotherapy can reduce the incidence of hematological toxicities compared with six cycles of adjuvant chemotherapy in endometrial cancer patients with a high risk of recurrence.